Organizational Vertical & Virtual Integration Model in Implementing Lean Manufacturing Transformation - Perumal, Puvanasvaran (Institue of Technology Management and Entrepreneurship, Universiti Teknikal Malaysia Melaka (UTeM), 2013)

(untitled)
At present-day, organizations face increasing global competitiveness and demands of the information and technological age, the need arises for integration of organizational structure and application system in order to achieve Lean manufacturing transformation. A broader set of skills, creative and innovative approaches to analysis, using up-to-date tools and design through the implementation of Lean manufacturing methodology are therefore important. The purpose of this paper is to integrate the organizational vertical and the virtual application in the conceptual framework from Lean manufacturing perspective through sensory modalities. This is to reduce some gaps that have been pointed out to Lean manufacturing transformation, namely, lack of ability to understand organizational structure and behavior, potentially negative impact on innovation capability and inability to eliminate waste in Lean manufacturing management. An integration Lean model is proposed in implementing Lean manufacturing transformation, thus enhancing problem solving capabilities and continuing improvement. The novelty of Organization Vertical and Virtual Integration model (OVVI) has parallels input values with other lean disciplines that providing quality information and effective information systems with special reference to Lean manufacturing in achieving organizational efficiency and accomplishment of application programs. The five sensory modalities applied to suite the real-time Lean process environment.